A Narrative Based Model of Differentiating Rioters. Issue 1 (1st February 2017) - WILLMOTT, DOMINIC; IOANNOU, MARIA
Abstract: The present study applied a narrative analysis upon rioter accounts of their motivations during the August 2011 England riots. To the authors' knowledge, this piece of research was the first to utilise narrative theory to explore the phenomenon of rioting. Narrative accounts of 20 rioters were compiled from media, online, and published sources. Content analysis of the cases produced a set of 47 variables relating to offenders' motivations given when describing their criminality. Data were subjected to Smallest Space Analysis (SSA), a non‐metric multidimensional scaling procedure, and results revealed four distinct themes: the Professional Rioter; the Revenger Rioter; the Victim Rioter; and the Adventurer Rioter, in line with previous research conducted on differing crime types (Canter, Kaouri and Ioannou 2003; Youngs and Canter 2011b). The four narrative themes are consistent with motivations identified in previous theories.